2020
DOI: 10.1007/s40616-019-00122-0
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Bidirectional Naming Through Sequential Operant Instruction Following the Establishment of Conditioned Social Reinforcers

Abstract: Bidirectional naming (BiN) is the integration of speaker and listener responses, reinforced by social consequences. Unfortunately, these consequences often do not function as reinforcers for behavior in children with autism. Accordingly, the repertoire of BiN is also often limited in these children. Previous research has suggested that so-called multiple-exemplar instruction, a rotation between different speaker and listener operants, may be necessary to establish BiN. The present experiment aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Potential implications for the role of echoic responding should be tempered in light of the issues described previously, as each of the three experiments had its own strengths and limitations. However, they fail to provide support for the notion that echoic responses during pairing are crucial to later tact emergence (Horne & Lowe, 1996), and as such, they are consistent with the results of other studies that have attempted to document this functional role (Byrne et al, 2014;Carp et al, 2015;Delfs et al, 2014;Haq et al, 2017;Olaff & Holth, 2020;Petursdottir et al, 2014). Anecdotally, some of the incorrect responses of our participants also seem to contradict this role of echoic responding.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Potential implications for the role of echoic responding should be tempered in light of the issues described previously, as each of the three experiments had its own strengths and limitations. However, they fail to provide support for the notion that echoic responses during pairing are crucial to later tact emergence (Horne & Lowe, 1996), and as such, they are consistent with the results of other studies that have attempted to document this functional role (Byrne et al, 2014;Carp et al, 2015;Delfs et al, 2014;Haq et al, 2017;Olaff & Holth, 2020;Petursdottir et al, 2014). Anecdotally, some of the incorrect responses of our participants also seem to contradict this role of echoic responding.…”
Section: Discussionsupporting
confidence: 64%
“…Others, however, have used stimulus pairing without a response requirement other than a prompt to observe the stimuli. Results have been variable within and across studies, but positive effects have been reported of interventions that include multiple-exemplar instruction (Gilic & Greer, 2011;Greer, Stolfi, Chavez-Brown, & Rivera-Valdes, 2005;Greer, Stolfi, & Pistoljevic, 2007;Hawkins, Kingsdorf, Charnock, Szabo, & Gautreaux, 2009;Olaff, Ona, & Holth, 2017), sequential operant instruction combined with the conditioning of social stimuli as reinforcers (Olaff & Holth, 2020), the conditioning of auditory and visual stimuli as reinforcers (Longano & Greer, 2014), and repeated exposure to stimulus pairing followed by tact testing .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings, albeit smaller in number, have been reported in the behavior-analytic literature. Olaff and Holth (2020), for example, conditioned social stimuli as reinforcers and found improvement during probes for BiN in their participants; critically, the procedure for conditioning social stimuli as reinforcers required the participants to engage in orienting toward the researcher, shifting gaze toward the researcher, or making eye contact with the researcher. Thus, these behaviors occurred more frequently after the training phase and could have affected the positive BiN results they obtained.…”
Section: The Concept Of Mutually Entailed Orienting As the Basis For ...mentioning
confidence: 99%
“…First, deficits in joint attention were clearly specifically linked to deficits in acquired reinforcement, supporting the hypothesis that such deficits are characteristic of autism. Second, acquired reinforcement emerged from an operant discrimination procedure, that is, one that established the target stimulus as a discriminative stimulus, rather than through stimulus–stimulus pairing (see also Holth et al, 2009; Olaff & Holth, 2020; Vandbakk et al, 2019). These results correlate well with the neurophysiological data suggesting a relationship between discriminative responding and activation of the n. accumbens.…”
Section: Acquired Reinforcement and Autismmentioning
confidence: 99%